Adoption of technologies that enhance soil carbon sequestration in East Africa: What influence farmers’ decision? - Karanja Ng'ang'a, Stanley; Anyango Jalang'o, Dorcas; Girvetz, Evan Hartunian (Elsevier, 2020)
"The last two decades have seen a rise of interest in the adoption and diffusion of agricultural technologies aimed at improving the sustainability of agricultural lands among smallholder farmers in developing countries. This papers set out to understand factors that influence the adoption of technologies that enhance soil carbon sequestration among smallholder farmers, using secondary data recorded in the World Overview of Conservation Approaches and Technologies (WOCAT) database from 45 to 50 smallholders’ farmers in selected places in Kenya and Ethiopia respectively. A Probit model was used to analyse whether socio-economic, institutional, off-farm income, technical know-how, farmers’ perceptions, and land use characteristics influences the adoption of technologies that enhance soil carbon sequestration. The results show that smallholder farmers that positively perceived net benefits of the soil carbon enhancing technologies were more likely to adopt such technologies that enhance soil carbon sequestration in both countries. Access to off-farm income and land ownership with title deeds were also found to be positively associated with adoption. Off-farm income positively influences adoption among farmer with a moderate income (100-500US$ per year) but not the rich (>500US$) farmers. Moderate to high level of skills and technical know-how required for implementing and maintaining a technology on the farm had a negative influence on adoption. This shows that interventions, aimed at addressing specific factors such as inadequate skills and knowledge, change in perception among farmers, and off-farm income are likely to have the greatest impact in decisions relating to the adoption of the soil carbon enhancing practices among farmers in East Africa.